The Existence of Mediation in Divorce Petition Cases from the Perspective of Islamic Law: An Empirical Study at the Religious Court of Gorontalo - Lisa Akhzan; Supiandi Supiandi (Econetica: Jurnal Sosial, Ekonomi, dan Bisnis, 2024)
This study examines the existence and practical implementation of mediation in divorce petition cases (cerai talak) from the perspective of Islamic law, using empirical evidence from the. Religious Court of Gorontalo, Indonesia. Mediation serves as a mandatory procedural step in religious court proceedings, intended to reconcile disputing spouses before a formal divorce decree is issued. However, its practical effectiveness in achieving reconciliation remains questionable. Using a qualitative empirical approach, data were collected through interviews with judges, mediators, and litigants, along with direct observations of mediation sessions. The findings reveal that mediation in divorce petitions is often conducted merely as a procedural formality to fulfill administrative requirements, rather than as a substantive effort to restore marital harmony. This condition arises due to several factors, including limited mediator engagement, insufficient understanding of Islamic reconciliation principles (al-ṣulḥ and iṣlāḥ), and a lack of emotional readiness among disputing parties. From the perspective of Islamic law, mediation is an embodiment of the Qur’anic injunctions in Surah An-Nisa (4:35), which emphasize peaceful settlement through arbitration and goodwill. The study highlights the need to strengthen the role of mediators as agents of reconciliation by integrating Islamic ethical and spiritual dimensions into the mediation process. It concludes that a reform of mediation practices in religious courts—through enhanced training, religious awareness, and procedural refinement—is essential to uphold the essence of islah as envisioned in Islamic jurisprudence